2021
DOI: 10.1021/acs.jchemed.0c01368
|View full text |Cite
|
Sign up to set email alerts
|

Sign Language Incorporation in Chemistry Education (SLICE): Building a Lexicon to Support the Understanding of Organic Chemistry

Abstract: Historically, deaf and hard-of-hearing students (D/HH) who solely rely on an interpreter during organic chemistry lecture courses at the Rochester Institute of Technology consistently performed below the average in the class. A barrier attributed to this D/HH student performance is the lack of standardized methods in sign language to effectively communicate the organic chemistry terminology. As such, our group worked to address this challenge through a deliberate effort to develop a lexicon of insightful signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Typical examples of chemistry courses that have introduced DEI-based activities in the classroom are General Chemistry, , Analytical Chemistry, , and Biochemistry with limited studies on DEI-related strategies for undergraduate Organic Chemistry courses, , despite the latter being a popular course for both Chemistry majors and nonmajors. Organic Chemistry course content includes fascinating molecules that can be easily linked with interesting stories to highlight the historical and intellectual achievements of women and chemists of color.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples of chemistry courses that have introduced DEI-based activities in the classroom are General Chemistry, , Analytical Chemistry, , and Biochemistry with limited studies on DEI-related strategies for undergraduate Organic Chemistry courses, , despite the latter being a popular course for both Chemistry majors and nonmajors. Organic Chemistry course content includes fascinating molecules that can be easily linked with interesting stories to highlight the historical and intellectual achievements of women and chemists of color.…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%
“…Over the years, colleges and universities have taken various approaches to better understand and meet the needs of students with marginalized or underrepresented socioeconomic and cultural identities. Despite efforts to diversify faculty and student populations, representation remains a primary issue outside of historically Black colleges and universities (HBCUs). Observable changes in racial diversity may contribute to an increased sense of belonging and student satisfaction, but some experiences of exclusion and marginalization cannot be redressed by institution-wide policies. ,− Students arrive on campus already carrying adverse childhood experiences, varying access to educational opportunities, and unpredictable prior relationships with academic mentors. ,,, These factors are known to affect student self-efficacy and, subsequently, students’ likelihood of success in higher education. Mainstream acknowledgment of the impact of these factors is supported by the shift away from SAT, ACT, and other standardized exams as predictors of student collegiate success. Harmful experiences for marginalized students, staff, and faculty also persist on our campuses, including experiences of tokenization, microaggressions, race-lighting, , and other covert forms of racism. These individuals are susceptible to racial battle fatigue, , a condition characterized by the accumulation of stress over time from frequent overt and implicit forms of discrimination.…”
Section: Intersection Of Education and Social Justicementioning
confidence: 99%